The association of extreme environmental heat with incidence and outcomes of out-of-hospital cardiac arrest in British Columbia: A time series analysis - Laiba Khan; Takahisa Kawano; Jacob Hutton; Michael Asamoah-Boaheng; Frank X. Scheuermeyer; Michael Christian; Leon Baranowski; David Barbic; Jim Christenson; Brian Grunau (Resuscitation Plus, 2024)
Background: The impact of extreme heat on out-of-hospital cardiac arrest (OHCA) incidence and outcomes is under-studied. We investigated OHCA incidence and outcomes over increasing temperatures. Methods: We included non-traumatic EMS (Emergency Medical Services)-assessed OHCAs in British Columbia during the warm seasons of 2020–2021. We fit a time-series quasi-Poisson generalized linear model to estimate the association between temperature and incidence of both EMS-assessed, EMS-treated, and EMS-untreated OHCAs. Second, we employed a logistic regression model to estimate the association between “heatwave” periods (defined as a daily mean temperature > 99th percentile for ≥ 2 consecutive days, plus 3 lag days) with survival and favourable neurological outcomes (cerebral performance category ≤ 2) at hospital discharge. Results: Of 5478 EMS-assessed OHCAs, 2833 were EMS-treated. OHCA incidence increased with increasing temperatures, especially exceeding a daily mean temperature of 25 °C Compared to the median daily mean temperature (16.9 °C), the risk of EMS-assessed (relative risk [RR] 3.7; 95%CI 3.0–4.6), EMS-treated (RR 2.9; 95%CI 2.2–3.9), and EMS-untreated (RR 4.3; 95%CI 3.2–5.7) OHCA incidence were higher during days with a temperature over the 99th percentile. Of EMS-treated OHCAs, during the heatwave (n = 179) and non-heatwave (n = 2654) periods, 4 (2.2%) and 270 (10%) survived and 4 (2.2%) and 241 (9.2%) had favourable neurological outcomes, respectively. Heatwave period OHCAs had decreased odds of survival (adjusted OR 0.28; 95%CI 0.10–0.79) and favourable neurological outcome (adjusted OR 0.31; 95%CI 0.11–0.89) at hospital discharge, compared to other periods. Conclusion: Extreme heat was associated with a higher incidence of OHCA, and lower odds of survival and favourable neurological status at hospital discharge.